Improving physicochemical and nutritional attributes of rice starch through green modification techniques - Rostamabadi, Hadis; Yildirim-Yalcin, Meral; Demirkesen, Ilkem; Toker, Omer Said; Colussi, Rosana; do Nascimento, Lucas Avila; Sahin, Selin; Falsafi, Seid Reza (ELSEVIER SCI LTD, 2024)
Rice, has long been an inseparable part of the human diet all over the world. As one of the most rapidly growing crops, rice has played a key role in securing the food chain of low-income food-deficit countries. Starch is the main component in rice granules which other than its nutritional essence, plays a key role in defining the physicochemical attributes of rice-based products. However, rice starch suffers from weak techno-functional characteristics (e.g., retrogradability of pastes, opacity of gels, and low shear/temperature resistibility. Green modification techniques (i.e. Non-thermal methods, Novel thermal (e.g., microwave, and ohmic heating) and enzymatic approaches) were shown to be potent tools in modifying rice starch characteristics without the exertion of unfavorable chemical reagents. This study corroborated the potential of green techniques for rice starch modification and provided deep insight for their further application instead of unsafe chemical methods.
Keywords: Rice; Starch digestibility; Thermal processing method; Non -thermal processing; Enzymatic modification; HIGH-HYDROSTATIC-PRESSURE; WAXY RICE; RHEOLOGICAL PROPERTIES; STRUCTURAL-PROPERTIES; FUNCTIONAL-PROPERTIES; QUALITY ATTRIBUTES; SUPERCRITICAL CO2; GAMMA-IRRADIATION; DIGESTIBILITY; IMPACT; Chemistry; Food Science & Technology; Nutrition & Dietetics